2021
DOI: 10.1016/j.micinf.2021.104810
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged viral shedding and antibody persistence in patients with COVID-19

Abstract: SARS-CoV-2 as a new global threat has affected global population for one year. Despite the great effort to eradicate this infection, there are still some challenges including different viral presentation, temporal immunity in infected individuals and variable data of viral shedding. We studied 255 COVID-19 suspected individuals to assess the viral shedding duration and also the antibody development against SARS-CoV-2 among the cases. Real Time RT-PCR assay was applied to determine the virus presence and SARS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…In contrast, our investigation showed the stability of anti-SARS-CoV-2 antibodies against nucleocapsid protein up to 25-30 weeks. Data similar to our results showing the increase of antibody levels were in another study analyzing 5 month humoral response (2021) 25 . Summarizing our data, we con rm that the level of anti-SARS-CoV-2 neutralizing antibodies takes bell-shaped character, continuously growing up to 5-6 months, remaining stable for a few months and slowly decreasing, but remaining to be detectable up to 60 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, our investigation showed the stability of anti-SARS-CoV-2 antibodies against nucleocapsid protein up to 25-30 weeks. Data similar to our results showing the increase of antibody levels were in another study analyzing 5 month humoral response (2021) 25 . Summarizing our data, we con rm that the level of anti-SARS-CoV-2 neutralizing antibodies takes bell-shaped character, continuously growing up to 5-6 months, remaining stable for a few months and slowly decreasing, but remaining to be detectable up to 60 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…The studies which focus on characterizing COVID-19-related immunity have shown that binding and neutralizing antibodies developed in response to SARS-CoV-2 infection and could provide protection up to six months after the onset of symptoms. Antibody titers establishment as a correlated factor with protection should be defined as a protective element which would be extremely critical for both patient management and public health considerations [ 7 , 8 ]. In fact, the importance of re-infection determination in a community can reflect the quarantine policy and vaccine development strategies.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have shown antibodies persisting for long periods. A study in Iran showed Ig G was still present after 150 days in 84% of the patients [ 18 ]. Another study, by Isho et al, showed Ig G lasting in serum for at least 90 days [ 19 ].…”
Section: Discussionmentioning
confidence: 99%